2003
DOI: 10.1046/j.1462-2920.2003.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Method of DNA extraction and application of multiplex polymerase chain reaction to detect toxigenic Vibrio cholerae O1 and O139 from aquatic ecosystems

Abstract: Vibrio cholerae is a free-living bacterium found in water and in association with plankton. V. cholerae non-O1/non-O139 strains are frequently isolated from aquatic ecosystems worldwide. Less frequently isolated are V. cholerae O1 and V. cholerae O139, the aetiological agents of cholera. These strains have two main virulence-associated factors, cholera toxin (CT) and toxin co-regulated pilus (TCP). By extracting total DNA from aquatic samples, the presence of pathogenic strains can be determined quickly and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
25

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 58 publications
(66 reference statements)
1
68
0
25
Order By: Relevance
“…DNA was extracted using a modification of the method of Rivera et al (47). The differences were as follows: the cell pellet was resuspended in 360 l SET buffer (20% [wt/vol] sucrose, 50 mM Tris-HCl [pH 8.0], 50 mM EDTA), and the volumes of all solutions added thereafter were one-fifth the original volumes described (47). The quality and quantity of the DNA extracted from the surface-colonizing microbes were determined by electrophoresis on 0.8% (wt/vol) agarose gels in 0.5ϫ Tris-borate-EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted using a modification of the method of Rivera et al (47). The differences were as follows: the cell pellet was resuspended in 360 l SET buffer (20% [wt/vol] sucrose, 50 mM Tris-HCl [pH 8.0], 50 mM EDTA), and the volumes of all solutions added thereafter were one-fifth the original volumes described (47). The quality and quantity of the DNA extracted from the surface-colonizing microbes were determined by electrophoresis on 0.8% (wt/vol) agarose gels in 0.5ϫ Tris-borate-EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro and in vivo studies showed that VBNC cells continue to be metabolically active, retain pathogenic potential but do not grow and do not form a colony on traditional culture media (57). VBNC bacteria can be detected in biological samples by culture-independent methods only (e.g., immunofluorescence, PCR) (58,59,60). Under favorable conditions (such as a rise in temperature), reversion from the VBNC to the culturable state can take place (56,61).…”
Section: Effect Of Increasing Sst On Vibrio Growth and Biology: Fieldmentioning
confidence: 99%
“…Samples were thawed at room temperature, and total nucleic acids were extracted and purified using methods described previously by Rivera et al [36]. Crude DNA was purified with the WIZARD DNA Clean Up System (Promega).…”
Section: Extraction Of Genomic Dna and Pcr Amplification Of Bacterialmentioning
confidence: 99%